Evaluation of IL-38, a Newly-Introduced Cytokine, in Sera of Vitiligo Patients and Its Relation to Clinical Features - Maryam Zarrabi; Nasser Gholijani; Zahra Amirghofran; Maryam Sadat Sadati; Roya Radanfar (Mattioli1885, 2024)
Introduction: Vitiligo is thought to be an autoimmune disorder caused by melanocytes dysfunction and depigmentation. Among different executors of the immune system in developing the disease, the role of various cytokines has been defined. Objectives: We have focused on IL-38, the tenth member of IL-1 cytokine family with a proposed anti-inflammatory role, which has not hitherto been introduced as an anti-inflammatory factor in vitiligo. Methods: Sixty-nine generalized vitiligo patients and 72-year-old- and sex-matched healthy individuals were included in this study. IL-38 level was evaluated in sera of all participants using ELISA assay. The relation of IL-38 level to patients characteristics was evaluated. Results: IL-38 serum level in vitiligo patients (159.5±39.7 pg/ml) was lower than the healthy controls (166.7±34.8pg/ml) (P = 0.039). A weak negative correlation between the age of male patients and their IL-38 serum levels was identified (r = 0.38, P = 0.058). Evaluation of the IL-38 serum levels relationship with patients clinical characteristics showed no correlation with disease onset, stage of depigmentation, and disease activity status. Conclusions: The lower levels of IL-38 as an anti-inflammatory cytokine support the inflammatory nature of vitiligo. It indicates the difference of IL-38 in sera of vitiligo patients and healthy controls, as the first report of the lower level of this cytokine in the context of vitiligo. The reason of this difference remains to be clarified; as there are not sufficient study reports revealing the role of gender, ethnicity and inflammation on the cytokine network in the context of vitiligo.